Web counselling as a recent advancement in technology: perspectives of practitioners in India - Sayyidath, Bayana Beevi Ottamaliyakkal; Menon, Sukanya B. (International Journal Of Community Medicine And Public Health, 2019)
Background: Online mental health treatment is an emerging, area and few professionals currently use the Internet to provide mental health services. At this time, mental health professions are lacking conclusive evidence about the effectiveness of these Internet services. The objective of the present study is to explore the nature and extent of online counselling in India. Methods: The study relies on data collected through semi-structured interview from e-Counsellors (n=15) and site admins (n=3) from India. The collected data were thematically coded and analyzed quantitatively. Results: Participants reported specific concerns and stereotypes related to the provision of mental health treatment online, including confidentiality of client information, liability issues, and limitations. Also, conveyed benefits of e-Counselling and suggestions for professionals for practicing on e-platforms. Conclusions: Participants reported specific concerns and stereotypes related to the provision of mental health treatment online, including confidentiality of client information, liability issues, and limitations. Also, conveyed benefits of e-Counselling and suggestions for professionals for practicing on e-platforms.